Teorie dell’argomentazione e scelte democratiche. Una critica interna al dibattito italiano / Argumentation Theory and Democratic Choices. Criticizing the Italian Debate from the Inside - Tambassi, Timothy (Rivista Italiana di Filosofia del Linguaggio)
The purpose of the article is to analyze the relationship among the argumentation theory, its fallacies and democratic choices by reference to public contests. Firstly, the aim will be pursued in accordance with what has been suggested in the Italian debate by Franca D’Agostini and Paola Cantù. In nutshell, the main thesis proposed by the authors holds that the argumentation theory might have an influence on the electors’ opinion and, consequently, might condition their democratic choices. All this considered, in the second place, the limits of that perspective will be pointed out and its grounding assumptions will be critically discussed